Integration of a Neurosignals System to Detect Human Expressions in the Multimedia Material Analysis (2014)
This paper presents the advances in the integration of a commercial low-cost device for capturing neural signals of a user. The idea is to record some expressions of a multimedia material user. Everyone performs various types of expressions watching TV, movies, ads or others external signals. Within these expressions can be highlighted some examples as: the clenching one's teeth with suspense scenes, moving one's head back when feeling an object is thrown out of the screen in one's direction dunging 3D movies, looking away during horror scenes, smiling in emotional trading, to laughter during humorous scenes or even fall asleep when there is disinterest. The general idea of this system is to capture all these expressions, together with emotive signals such as the level of attention, frustration and meditation, in order that the experts designers of multimedia material, can analyze and improve their products Experimental evidence is presented showing the good performance of the system.